2020
DOI: 10.2147/idr.s257145
|View full text |Cite
|
Sign up to set email alerts
|

<p>Genetic and Virulence Characteristics of Linezolid and Pretomanid Dual Drug-Resistant Strains Induced from <em>Mycobacterium tuberculosis</em> in vitro</p>

Abstract: Purpose: Linezolid (LZD) and pretomanid (PA-824) are promising candidates in regimens for the treatment of drug-resistant tuberculosis. However, research on LZD and PA-824 dual drug-resistant (LPDR) strains is rarely reported. This study aimed to investigate the genotypic and virulence characteristics of LPDR strains. Methods: To obtain the LPDR strains (marked as LP or PL strains), we used a two-way induction method, namely, we first induced LZD-or PA-824-resistant mutants from the parental Mycobacterium tube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…LNZ has exhibited an excellent anti-mycobacterial effect and several studies have shown that it is an effective third-line antibiotic for the treatment of the MDR-and XDR-TB patients, with favorable outcomes [11][12][13]. It is now classified as group A, the preferred drug group for MDR-TB and rifampin-resistant TB treatment that plays a critical role in the treatment of drug-resistant TB [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…LNZ has exhibited an excellent anti-mycobacterial effect and several studies have shown that it is an effective third-line antibiotic for the treatment of the MDR-and XDR-TB patients, with favorable outcomes [11][12][13]. It is now classified as group A, the preferred drug group for MDR-TB and rifampin-resistant TB treatment that plays a critical role in the treatment of drug-resistant TB [7,14].…”
Section: Introductionmentioning
confidence: 99%